Multifunctionality of Mediasphere in Problematization of Social Contradictions - Bolshakov, Sergey Nikolaevich; Mikhalchenkova, Natalya Alekseevna; Istikhovsaya, Marina Dmitrievna; Bolshakova, Yulia Mikhalovna (International Review of Management and Marketing, 2015)
The article analyzes the functions and dysfunctions of mass media in modern society, states the communicative essence of problematization of the contradictions existing in society. The main purpose of the article is to analyze the functions of Media communications concerning socially significant problems that reflect the contradictions existing in the society. As a part of the structural and functional analysis, we have come to the conclusion that the problematization of social contradictions is considered as the result of interactions between individual and collective social subjects, taking place in the social environment that has a systemic character. The authors identified nine basic functions of modern media sphere in the construction of socially significant problems. Keywords: social problems, mass media, social structures, social interests, social contradictions, communications. JEL Classifications: Z13